Encyclopedia of associations. International organizations. - Gale Research Inc. (Detroit, Mich. Gale Research, 1989)
"A guide to over ... international nonprofit membership organizations including multinational and binational groups, and national organizations based outside the United States, concerned with all subjects or areas of activity."
Latest issue consulted: 34th ed., published in 1999.
Issues for 1989-2002 issued in 2 pts.: pt. 1, Descriptive listings; pt. 2, Indexes.
Issues for 2003- issued in 3 pts.: pt. 1, Descriptive listings, Sections 1-5; pt. 2, Descriptive listings, Sections 6-15; pt. 3, Indexes.
System requirements for accompanying CD-ROM: 80386 or higher IBM/IBM compatible PC (486 recommended); 8MB of RAM; 10 MB free HD space; Windows 3.1 or higher with DOS 5.0 or higher; Microsoft CD extensions (MSCDEX) 2.2 or higher; SVGA graphics card and monitor; Mouse or pointing device.
Also available as part of CD-ROM: Encyclopedia of associations CD-ROM, <1992->
Vols. for <1998-> accompanied by the International organizations CD-ROM module of: Associations unlimited, the full version of which is also available online.
Keywords: International agencies -- Directories; Associations, institutions, etc. -- Directories; International Agencies -- Directory; Organizations -- Directory; Societies -- Directory